IS IT ENJOYING OR BURDENING? STUDENTS’ PERCEPTIONS ON HOME LEARNING AND ONLINE LEARNING (An Overview of Corona Virus Disease “COVID-19” Impact to Education Field) - Olbata, Yabes; Fatmawati, Ririn; Tiran, Yessy (Universitas Wiralodra, 2022)
Teaching and learning is a good way to reach the educational goals. Since the Corona Virus Disease (COVID-19) hits the word, the process of teaching and learning totally change that creates new problem for teachers and students. This study aims to find out the students’ perceptions of the implementation of home learning and online learning during the pandemic era (COVID-19) in SMA Negeri 1 Soe. This study used a qualitative descriptive design. The instruments used were questionnaires and interviews. The data of this study was collected through spreading questionnaires and doing interviews. The data of this study were analyzed by using SPSS. The result of the study showed that students perceive the implementation of home learning and online learning during pandemic era (COVID-19) is a good way because it could protect the students from the spread of the COVID-19, it helped the students to keep learning. It could make the students to be responsible for their learning improvement.